Vacuum assisted closure for defects of the abdominal wall after intestinal transplantation - Pinheiro, Rafael S.; Andraus, Wellington; Fortunato, Allana C.; Galvão, Flavio H. F.; Nacif, Lucas S.; Waisberg, Daniel R.; Arantes, Rubens M.; Lee, Andre D.; Rocha-Santos, Vinicius; Martino, Rodrigo B.; Ducatti, Liliana; Haddad, Luciana Bertocco de Paiva; et al. (Frontiers in Transplantation, 2022)
isolated intestinal transplantation (IT) is indicated in cases of intestinal failure (IF) in the absence of severe liver dysfunction. Short bowel syndrome (SBS) is the most frequent IF etiology, and due to the absence or considerable reduction of intestinal loops in the abdominal cavity in these patients, there is atrophy and muscle retraction of the abdominal wall, leading to loss of abdominal domain and elasticity and preventing the primary closure of the abdominal wall. The aim of this study is to describe an innovative technique for closure of the abdominal wall after IT without using prostheses. Methods: Four patients underwent IT with impossibility of primary closure of the abdominal wall. We describe a novel technique, associating a series of vacuum-assisted closure dressings, components separation and relaxation incisions. Results: All patients presented a successful closure of the abdominal wall with the described technique, with no complications related to the abdominal wall. Conclusion: the innovative technique proved to be safe, effective and reproducible, being an option for abdominal wall closure after IT. Employing this technique in a greater number of cases is necessary to confirm these results.